LEARNING LOSS IN THE TEACHING OF ENGLISH SUBJECT AT A VOCATIONAL SCHOOL IN TANJUNG JABUNG BARAT: TEACHERS' PERCEPTION - Rahayu, Silviah Dewi (Langue (Journal of Language and Education), 2022)
Abstract The covid-19 Pandemic has caused an unexpected shift in teaching and learning at schools around the world. The teaching and learning process has mostly switched to distance learning and causes problems for all parties involved, including students and their parents, teachers, and school management. While research has been carried out to observe the implementation of distance learning and its challenges and problems, only a few studies have been focused on investigating a possible phenomenon called ‘learning loss’. Learning loss is generally defined as a lack of student interest in the learning process because there is only little to zero direct interaction process during their learning. This research is designed to investigate the possible occurrence of learning loss in a vocational school in Tanjung Jabung Barat. The research was carried out qualitatively. Data were collected through in-depth interviews with participants that consist of two English teachers in the school. Questions addressed in the interview were focused on investigating the shift in the teachers’ teaching process and students’ learning activities, including the signs of a decrease or loss of interest in learning and the impact on learning achievement. Teachers’ understanding of students’ situations and efforts to mitigate them will also be investigated. Data collected from the interview was analyzed using theories relevant to the issues. Key Word: Pandemic, English Teaching, Teachers Perception, Learning Loss